Right Anterolateral Thoracotomy an Alternative to Median Sternotomy for Closure of Atrial Septal Defect: A Cosmetic Approach in Young Females - Baral, Ravi Kumar; Koirala, Bhagawan (Nepalese Heart Journal, 2015)
Background and Aims: Atrial septal defect operation is a safe and low-risk procedure. Cosmetic results have been an important issue, so right anterolateral thoracotomy approach has been used for repair. We present minimally invasive ASD closure via limited right anterolateral thoracotomy, as our early experience in road of minimally invasive cardiac surgery. Methods: This study was done in the Manmohan Cardiothoracic and Transplant Center in the time period of 2012 to 2013. The study included 70 patients aged 15 – 35 years old (22.1±5.5) admitted for surgical repair of their secundum atrial septal defects. The patients were randomly allocated into one of two groups according to the approach used in their operation. Right anterolateral thoracotomy(RALT) group included 35 patients operated via right anterolateral thoracotomy.and median sternotomy(MS) group included 35 patients operated via the median sternotomy. Result: Of 70 patients only 63 patients meet the criteria for analysis. There was no statistically significant difference between the 2 groups regarding their demographic data and duration of operation. Postoperative pleural/pericardial effusion and pneumothorax occurred in 2.1% of patients in MS and 6.6% in Right anterolateral thoracotomygroup (p= 0.001). Total in hospital pain score was high in sternotomy group than thoracotomy group, but did not reach statistically significant values. There was no operative or late mortality or morbidity in the early follow-up (range, 1 m to 2 years, mean 1.34 yrs). Conclusion: RALT is a safe and effective alternative approach to MS incision for ASD closure. DOI: http://dx.doi.org/10.3126/njh.v12i1.12340 Nepalese Heart Journal Vol.12(1) 2015: 21-25